High-purity nanometer monodispersed alumina and its preparation method

CN122897429APending Publication Date: 2026-10-13ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611361256.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0008]本申请提供了一种高纯纳米单分散氧化铝及其制备方法,以解决目前因煅烧过程中发生不可逆硬团聚、α相转变温度过高,导致难以在保持4N高纯度的前提下实现单分散纳米α-Al2O3的问题

Benefits of technology

1、本申请实施例提供的高纯纳米单分散氧化铝,该高纯纳米单分散氧化铝的纯度≥99.99%,且α-Al2O3相占比≥98%,粒径分布分散指数PDI≤0.10;这种纯度高、颗粒分散性优异、形貌规整能满足电子陶瓷、精密抛光等高端高纯粉体应用需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897429A_ABST
    Figure CN122897429A_ABST
Patent Text Reader

Abstract

The application relates to high-purity nanometer monodispersed alumina and a preparation method thereof, the high-purity nanometer monodispersed alumina has a purity of greater than or equal to 99.99%, contains greater than or equal to 98% of an alpha-Al2O3 phase, has an average primary particle size of 20-50 nm, a secondary particle size D50 of 50-100 nm, and a particle size distribution dispersion index of less than or equal to 0.10 50 The high-purity nanometer monodispersed alumina can meet the application requirements of high-end high-purity powder such as electronic ceramics and precision polishing; the preparation method is that an aluminum alcohol solution and a seed solution are placed in a microemulsion to perform a controllable hydrolysis reaction, then centrifugal demulsification, gradient calcination and purification treatment are performed, and finally high-purity nanometer monodispersed alumina with a purity of greater than or equal to 99.99% is prepared; the three synergistic mechanisms of space-limited hydrolysis of the microemulsion, superfine seed-induced directional crystal phase change and agglomeration prevention of the alkali-free metal salt molten salt isolation layer are relied on, and 4N-level monodispersed nanometer alpha-Al2O3 powder without hard agglomeration and with a spherical morphology is prepared under a relatively low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of inorganic material preparation technology, and in particular to a high-purity nano-monodisperse alumina and its preparation method. Background Technology

[0002] High-purity alumina (Al2O3 purity ≥ 99.99%, abbreviated as 4N) is a key basic material in LED lighting, new energy vehicles, high-end electronics and other fields. As a phosphor matrix, the purity of alumina directly affects luminous efficiency; as a ceramic coating for lithium battery separators, nano-alumina can significantly improve thermal stability and ionic conductivity; as a transparent ceramic raw material, monodisperse nanoparticles are a prerequisite for achieving high optical transmittance.

[0003] Currently, while vapor-phase methods (such as chemical vapor deposition (CVD) and laser ablation) can produce high-purity, monodisperse nano-alumina, they suffer from low yields, high energy consumption, and expensive equipment, making industrialization difficult. Liquid-phase methods, such as the sol-gel and precipitation methods, are easily scaled up, but they generally suffer from wide particle size distributions and uneven morphology. Furthermore, during drying and calcination, surface hydroxyl condensation and high-temperature sintering neck formation lead to severe irreversible hard agglomeration, resulting in secondary particle sizes reaching the micrometer scale and significantly degrading sintering activity.

[0004] The alkoxide hydrolysis method uses high-purity aluminum alkoxide as raw material and theoretically avoids metal ion contamination, making it an ideal route for preparing 4N grade alumina. However, aluminum isopropoxide is extremely prone to violent hydrolysis in water, forming amorphous boehmite aggregates; furthermore, it requires high-temperature calcination above 1200℃ to complete the α-phase transformation, which further exacerbates grain growth and hard agglomeration.

[0005] To suppress calcination agglomeration, current techniques attempt to introduce salt-isolating phases (such as KCl, K₂SO₄, etc.). While alkali metal salts can melt and isolate particles at high temperatures, Na… + / K + Salt readily diffuses into the Al2O3 crystal lattice and strongly adsorbs onto the surface hydroxyl groups, making it difficult to remove completely by water washing. This results in a decrease in product purity, failing to meet the requirements for 4N-grade high-purity alumina. Therefore, the use of salt isolation strategies is generally avoided in the field of high-purity alumina preparation.

[0006] In addition, current seed-induced phase transition technology mostly uses submicron-sized α-Al2O3 seeds with a diameter >100nm, which have a small contact area, low induction efficiency, and the seeds themselves are prone to becoming agglomeration nuclei. While the microemulsion method can confine hydrolysis, it often leads to carbon residue due to the introduction of a large amount of organic matter, making it difficult to prepare 4N-grade high-purity alumina.

[0007] In view of this, it is necessary to design a high-purity nano-monodisperse alumina and its preparation method to solve the above problems. Summary of the Invention

[0008] This application provides a high-purity monodisperse nano-alumina and its preparation method to solve the problem that it is difficult to achieve monodisperse nano-α-Al2O3 while maintaining high purity due to irreversible hard agglomeration during calcination and excessively high α-phase transformation temperature.

[0009] In a first aspect, this application provides a high-purity nano-monodisperse alumina, wherein the purity of the high-purity nano-monodisperse alumina is ≥99.99%; The high-purity nano-monodisperse alumina contains ≤50ppm Na2O, ≤30ppm Fe2O3, and ≤50ppm SiO2 by mass percentage. The high-purity nano-monodisperse alumina comprises ≥98% α-Al2O3 by mass percentage.

[0010] In some embodiments, the primary particles of the high-purity nano-monodisperse alumina have an average particle size of 20 nm to 50 nm, and the secondary particles of the high-purity nano-monodisperse alumina have a diameter of D... 50 Particle size of 50nm~100nm; and / or, The particle size distribution ratio D of the secondary particles of the high-purity nano-monodisperse alumina 90 / D 10 The ratio is <2.5; and / or, The high-purity nano-monodisperse alumina has a particle size distribution dispersion index (PDI) ≤ 0.10; and / or, The specific surface area of ​​the high-purity nano-monodisperse alumina is 30 m². 2 ·g -1 ~60m 2 ·g -1 .

[0011] Secondly, this application provides a method for preparing the above-mentioned high-purity nano-monodisperse alumina, comprising the following steps: An aluminum alkoxide solution, a seed crystal solution, and a microemulsion are provided. The aluminum alkoxide solution, the seed crystal solution, and the microemulsion are first mixed to obtain a composite phase mixture intermediate. The intermediate of the composite phase mixture is subjected to a controlled hydrolysis reaction to obtain a hydrolyzed mixture; The hydrolyzed mixture is mixed with the isolated phase to obtain a composite phase mixture; The composite phase mixture was centrifuged and demulsified to obtain a first solid phase, a first liquid phase, and an oil phase. The first solid phase is subjected to a first washing treatment and a spray drying treatment in sequence to obtain the precursor composite powder; The precursor composite powder was subjected to gradient calcination to obtain a high-purity nano-monodisperse alumina intermediate; and, The high-purity nano-monodisperse alumina intermediate was purified to obtain the high-purity nano-monodisperse alumina.

[0012] In some embodiments, the atmosphere for the gradient calcination treatment includes either an air atmosphere or an oxygen atmosphere; and / or, The gradient calcination process includes sequentially subjecting the precursor composite powder to a first calcination, a second calcination, and a third calcination. The heating rate of the first calcination is 2℃ / min to 5℃ / min; the calcination temperature of the first calcination is 400℃ to 500℃; and the calcination time of the first calcination is 1h to 2h. The heating rate of the second calcination is 3℃ / min~5℃ / min; the calcination temperature of the second calcination is 800℃~900℃; and the calcination time of the second calcination is 1h~2h. The heating rate of the third calcination is 6℃ / min~7℃ / min; the calcination temperature of the third calcination is 1080℃~1120℃; and the calcination time of the third calcination is 2.5h~3.5h.

[0013] In some embodiments, the first mixing method includes the following steps: simultaneously pumping the aluminum alkoxide solution and the seed crystal solution into the microemulsion through a dual-channel microreactor; The inner diameter of the dual-channel microreactor is 0.5 mm to 2.0 mm; The volumetric flow rate ratio of the aluminum alkoxide solution to the seed crystal solution is 1:(1.2~2.0); the residence time of the aluminum alkoxide solution in the dual-channel microreactor during the controlled hydrolysis reaction is 5 min~15 min; the residence time of the seed crystal solution in the dual-channel microreactor during the controlled hydrolysis reaction is 5 min~15 min; and / or, The pH value of the controlled hydrolysis reaction is 8.5~10.5; the pH value of the controlled hydrolysis reaction is adjusted by: adjusting the feed flow rate of the seed crystal solution; and / or, The controlled hydrolysis reaction is carried out at a temperature of 40℃~60℃; and / or, The controlled hydrolysis reaction takes place over a period of 1 to 3 hours; and / or, The controllable hydrolysis reaction is carried out under stirring conditions, and the stirring rate under stirring conditions is 300 rpm to 800 rpm.

[0014] In some embodiments, the isolating phase comprises ammonium sulfate; and / or, The molar ratio of the isolating phase to the aluminum ions in the aluminum alkoxide solution is (15~30):1; and / or, The stirring rate for the centrifugal demulsification process is 3000 rpm to 5000 rpm; and / or, The centrifugal demulsification process is performed for 5 to 10 minutes; and / or, The inlet temperature of the spray dryer is 180℃~220℃; and / or, The outlet temperature of the spray dryer is 80℃~100℃.

[0015] In some embodiments, the purification process includes the following steps: The high-purity nano-monodisperse alumina intermediate is subjected to a second washing treatment and an acid washing treatment to obtain a second solid phase and a second liquid phase. The second solid phase is subjected to a second centrifugation treatment and a second acid washing treatment to obtain a third solid phase and a third liquid phase; The third solid phase was freeze-dried to obtain the high-purity nano-monodisperse alumina. The reagents for both the first and second acid pickling treatments include an acid solution; the acid solution includes either dilute nitric acid or dilute hydrochloric acid; the pH value of the acid solution is 3-4; and the time for both the first and second acid pickling treatments is 10-30 minutes. The freeze-drying process is carried out at a temperature of -50℃ to -40℃, with a vacuum degree of ≤10Pa and a duration of 24h to 48h.

[0016] In some embodiments, the method for preparing the aluminum alkoxide solution includes the following steps: Aluminum metal was mixed with isopropanol and subjected to reflux and vacuum distillation sequentially to obtain aluminum isopropoxide; and, The aluminum isopropoxide is mixed with anhydrous isopropanol to obtain the aluminum alkoxide solution; Wherein, the purity of the aluminum metal is ≥99.999%; The vacuum degree of the vacuum distillation process is ≤100Pa; the fraction collected at 135℃~140℃ during the vacuum distillation process is used as aluminum isopropoxide; The purity of the aluminum isopropoxide is ≥99.999%; the total amount of Si, Fe, Na, Ca, Mg, Cu, Ti, Cr, Mn and Zn in the aluminum isopropoxide is ≤10ppm by mass percentage. The aluminum ion concentration in the aluminum alkoxide solution is 0.05 mol / L to 0.2 mol / L; The mass ratio of aluminum isopropoxide to anhydrous isopropanol is 1:(8~20).

[0017] In some embodiments, the seed solution includes an alkaline solution containing nano-alumina seeds, wherein the alkaline solution containing nano-alumina seeds includes an ammonia solution containing nano-alumina seeds. The preparation method of the ammonia solution containing nano-alumina seeds includes the following steps: mixing nano-alumina seeds with a first ammonia solution to obtain the ammonia solution containing nano-alumina seeds; The concentration of the first ammonia solution is 0.5 mol / L to 2.0 mol / L; the nano-alumina seed crystals are α-Al2O3 transparent hydrosols with a solid content of 5% to 10% and an average particle size of 5 nm to 20 nm; the mass ratio of Al2O3 in the nano-alumina seed crystals to the ammonia solution containing the nano-alumina seed crystals is (0.5 to 3):100.

[0018] In some embodiments, the method for preparing the microemulsion includes the following steps: A mixture was prepared by mixing a composite surfactant, cyclohexane, and a second ammonia solution; and, The mixture is ultrasonically emulsified, and then a co-surfactant is added to obtain the microemulsion. The composite surfactant comprises sorbitan monooleate and polyoxyethylene sorbitan monooleate; the mass ratio of sorbitan monooleate to polyoxyethylene sorbitan monooleate is (3~5):1. The mass ratio of the composite surfactant to the cyclohexane is (5~12) g: 100 mL; The total volume ratio of the composite surfactant and the second ammonia water to the volume ratio of the cyclohexane is 1:(8~15); The concentration of the second ammonia solution is 0.0455 mol / L to 0.4286 mol / L; The temperature for ultrasonic emulsification is 30℃~40℃; The ultrasonic emulsification time is 10 min to 30 min; The power of the ultrasonic emulsification is 200W~400W; The frequency of the ultrasonic emulsification is 40 kHz; The average particle size of the micro-water nuclei in the microemulsion is 10 nm to 20 nm. The co-surfactant includes polyethylene glycol 400; The mass ratio of the co-surfactant to the cyclohexane is (1~3) g: 100 mL.

[0019] The technical solutions provided in this application have the following advantages compared with the prior art: 1. The high-purity nano-monodispersed alumina provided in this application embodiment has a purity of ≥99.99%, an α-Al2O3 phase ratio of ≥98%, and a particle size distribution dispersion index (PDI) of ≤0.10. This high purity, excellent particle dispersibility, and regular morphology can meet the application requirements of high-end high-purity powders such as electronic ceramics and precision polishing.

[0020] 2. The above-mentioned method for preparing high-purity nano-monodisperse alumina also provided in the embodiments of this application involves placing an aluminum alkoxide solution and a seed crystal solution in a microemulsion for a controlled hydrolysis reaction, followed by centrifugal demulsification, gradient calcination, and purification treatment to finally obtain high-purity nano-monodisperse alumina with a purity ≥99.99%. Among them, relying on the triple synergistic mechanism of microemulsion spatial confinement hydrolysis, ultrafine seed crystal-induced directional crystal phase transformation, and alkali-free metal salt molten salt isolation layer to prevent agglomeration, 4N-level monodisperse nano-α-Al2O3 powder with no hard agglomeration and spherical morphology is prepared under relatively low temperature conditions. Attached Figure Description

[0021] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0022] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 This image shows a transmission electron microscope morphology of an α-Al2O3 transparent hydrosol provided in Embodiment 1 of this application; Figure 2 The image shown is a field emission electron microscope morphology image of a high-purity nano-monodisperse alumina provided in Embodiment 1 of this application. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0025] Various embodiments of this application may exist in the form of a range. It should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of this application. Therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated in this application, it means including any referenced number (fraction or integer) within the indicated range. Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in this application can be purchased commercially or prepared by existing methods. In this application, unless otherwise stated, directional terms such as "upper" and "lower" specifically refer to the drawing directions in the accompanying drawings. In addition, in this application, the terms "comprising," "including," etc., mean "including but not limited to." In this application, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, without necessarily requiring or implying any actual relationship or order between these entities or operations. In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A alone, A and B simultaneously, or B alone. A and B can be singular or plural. In this application, "at least one" means one or more, and "more than one" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c," or "at least one of a, b, and c," can both represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can each be single or multiple.

[0026] This application provides a high-purity nano-monodisperse alumina, wherein the purity of the high-purity nano-monodisperse alumina is ≥99.99%; By mass percentage, the high-purity nano-monodisperse alumina contains ≤50ppm Na2O, ≤30ppm Fe2O3, and ≤50ppm SiO2.

[0027] The high-purity nano-monodisperse alumina comprises ≥98% α-Al2O3 by mass percentage.

[0028] The high-purity nano-monodispersed alumina provided in this application has high purity, excellent particle dispersibility, and regular morphology, which can meet the needs of high-end high-purity powder applications such as electronic ceramics and precision polishing.

[0029] As an optional implementation, in this embodiment of the application, the laser particle size analyzer test results show that the average particle size of the primary particles of the high-purity nano-monodisperse alumina is 20nm~50nm, and the secondary particle size of the high-purity nano-monodisperse alumina is D... 50 The particle size distribution ratio D of the secondary particles of the high-purity nano-monodisperse alumina is 50nm~100nm. 90 / D 10 The ratio is less than 2.5; The particle size distribution dispersion index (PDI) of the high-purity nano-monodisperse alumina is ≤0.10; The specific surface area of ​​the high-purity nano-monodisperse alumina is 30 m². 2 ·g -1 ~60m 2 ·g -1 .

[0030] Based on a general inventive concept, this application provides a method for preparing the above-mentioned high-purity nano-monodisperse alumina, comprising the following steps: Step 1: Provide aluminum alkoxide solution, seed crystal solution, and microemulsion; Step 2: The aluminum alkoxide solution, the seed crystal solution, and the microemulsion are mixed for the first time to obtain a composite phase mixture intermediate; Step 3: Perform a controlled hydrolysis reaction on the intermediate of the composite phase mixture to obtain a hydrolyzed mixture; mix the hydrolyzed mixture with the separating phase to obtain a composite phase mixture; Step 4: Centrifuge the composite phase mixture to demulsify it, and obtain a first solid phase, a first liquid phase, and an oil phase; Step 5: Perform a first washing treatment and a spray drying treatment on the first solid phase in sequence to obtain the precursor composite powder; Step 6: Perform gradient calcination on the precursor composite powder to obtain a high-purity nano-monodisperse alumina intermediate; Step 7: Purify the high-purity nano-monodisperse alumina intermediate to obtain the high-purity nano-monodisperse alumina.

[0031] This application provides a method for preparing high-purity nano-monodisperse alumina. The method involves placing an aluminum alkoxide solution and a seed crystal solution in a microemulsion for controlled hydrolysis, followed by centrifugal demulsification, gradient calcination, and purification to ultimately obtain high-purity nano-monodisperse alumina with a purity ≥99.99%. The method utilizes a triple synergistic mechanism of microemulsion spatial confinement hydrolysis, directional crystal phase transformation induced by ultrafine seeds, and an alkali-free molten salt isolation layer to prevent agglomeration. This allows for the preparation of 4N-level monodisperse nano-α-Al₂O₃ powder with no hard agglomeration and a spherical morphology under relatively low temperature conditions.

[0032] As an optional implementation, in this embodiment of the application, the method for preparing the aluminum alkoxide solution in step one includes the following steps: Aluminum isopropanol is mixed with aluminum and subjected to reflux reaction and vacuum distillation in sequence to obtain aluminum isopropoxide. The aluminum isopropoxide solution is obtained by mixing it with anhydrous isopropanol.

[0033] In this embodiment, the purity of the metallic aluminum is ≥99.999%; the vacuum degree of the vacuum distillation process is ≤100Pa; the fraction collected at 135℃~140℃ during the vacuum distillation process is used as the aluminum isopropoxide; the purity of the aluminum isopropoxide is ≥99.999%; the total amount of Si, Fe, Na, Ca, Mg, Cu, Ti, Cr, Mn, and Zn in the aluminum isopropoxide is ≤10ppm by mass percentage; the aluminum ion concentration in the aluminum alkoxide solution is 0.05mol / L~0.2mol / L; and the mass ratio of the aluminum isopropoxide to the anhydrous isopropanol is 1:(8~20).

[0034] In this embodiment of the application, the reflux reaction time is 24h~26h.

[0035] In the embodiments of this application, a catalyst may be added during the reflux reaction, and the catalyst includes at least one of aluminum amalgam, aluminum chloride, and aluminum isopropoxide.

[0036] Thus, high-purity aluminum isopropoxide with a purity of ≥99.999% is obtained.

[0037] As an optional implementation, in this embodiment of the application, the seed solution includes an alkaline solution containing nano-alumina seeds, and the alkaline solution containing nano-alumina seeds includes an ammonia solution containing nano-alumina seeds.

[0038] As an optional implementation, in this embodiment of the application, the method for preparing the ammonia solution containing nano-alumina seeds includes the following steps: mixing nano-alumina seeds with a first ammonia solution to obtain the ammonia solution containing nano-alumina seeds. Wherein, the concentration of the first ammonia solution is 0.5 mol / L to 2.0 mol / L; the nano-alumina seed crystals are α-Al2O3 transparent hydrosols with an average particle size of 5 nm to 20 nm; the mass ratio of Al2O3 in the nano-alumina seed crystals to the ammonia solution containing the nano-alumina seed crystals is (0.5~3):100.

[0039] Thus, by using ammonia solution with a concentration of 0.5 mol / L to 2.0 mol / L, combined with α-Al₂O₃ transparent hydrosol with an average particle size of 5 nm to 20 nm as seed crystals, and controlling the mass ratio of Al₂O₃ to the ammonia solution containing nano-alumina seed crystals in the seed crystals to be (0.5~3):100, the technical effect of highly efficient phase transformation induced by ultrafine seed crystals can be achieved. The mechanism of ultrafine seed crystal induction is as follows: Ultrafine α-Al₂O₃ seeds with a particle size of 5 nm to 20 nm can achieve nanoscale tight adhesion with aluminum alkoxide solution within a microemulsion microaqueous core, forming stable homogeneous epitaxial growth sites. According to classical nucleation theory, the seeds can provide a matching α-Al₂O₃ lattice template, transforming the α-crystal transformation of transition phase alumina from high-barrier homogeneous nucleation to low-barrier heteroepitaxial growth, thereby reducing the system's nucleation barrier by 30% to 50%.

[0040] As an optional implementation, in this embodiment of the application, the method for preparing the nano-alumina seed crystals includes the following steps: 1) Boehmite, polyethylene glycol and deionized water were mixed at a mass ratio of 1:(0.005~0.02):(20~50), and then subjected to first ultrasonic dispersion and hydrothermal treatment in sequence to obtain boehmite nanosheet precursor. Wherein, the first ultrasonic dispersion time is 30min~40min, and the power of the first ultrasonic dispersion is 300W~500W; The hydrothermal treatment temperature is 180℃~200℃; the hydrothermal treatment time is 12h~24h; and the filling degree of the hot reactor used for the hydrothermal treatment is 70%~80%. 2) The boehmite nanosheet precursor was subjected to centrifugal washing and freeze-drying treatment in sequence to obtain fluffy boehmite powder; The centrifugal washing process is carried out at a speed of 8000 r / min to 12000 r / min; the freeze-drying process is carried out at a temperature of -55℃ to -40℃; and the freeze-drying process is carried out for a time of 24 h to 48 h. 3) The boehmite powder is mixed with an ammonium salt aqueous solution and placed in a high-purity alumina crucible for calcination to obtain a nano-alumina seed intermediate; The ammonium salt aqueous solution includes an ammonium sulfate solution with a molar concentration of 0.3 mol / L to 1.5 mol / L; the mass ratio of boehmite powder to ammonium sulfate solution is 1 g:(5~15) mL; the calcination treatment is carried out in an air atmosphere; the heating rate of the calcination treatment is 3℃ / min to 5℃ / min; the calcination temperature of the calcination treatment is 950℃ to 1050℃; the calcination time of the calcination treatment is 2h to 4h; and the primary particle size of the nano-alumina seed intermediate is 30nm to 60nm. Thus, during the calcination process, boehmite undergoes a crystal transformation to generate α-Al2O3; ammonium sulfate in the system melts upon heating and uniformly coats the particle surface, effectively suppressing high-temperature coarsening of the grains by relying on the spatial barrier effect of the molten salt film, and ultimately the primary particle size of the product can be stably controlled in the range of 30nm~60nm.

[0041] 4) The nano-alumina seed intermediate is subjected to a fourth washing treatment to obtain a pure nano-alumina seed intermediate; The fourth washing process includes washing with deionized water 3 to 5 times. 5) The pure nano-alumina seed intermediate, sodium hexametaphosphate, and solvent are mixed and then subjected to a second ultrasonic dispersion and ball milling process to obtain a dispersion slurry. The solvent one comprises deionized water; the mass ratio of sodium hexametaphosphate, α-Al2O3 in the pure nano-alumina seed intermediate, and solvent two is (1~3):100:(300~500); the power of the second ultrasonic dispersion is 300W~500W; the time of the second ultrasonic dispersion is 1h~2h; the grinding medium for ball milling includes zirconia balls, the ball-to-material ratio for ball milling is (5~10):1, the dispersion medium for ball milling includes ethanol, the ball milling speed for ball milling is 200rpm~400rpm, and the ball milling time for ball milling is 6h~12h; 6) Mix the dispersion slurry with deionized water at a mass ratio of 1:(8~12), and perform a third ultrasonic dispersion and a first centrifugation treatment in sequence. Take the supernatant to obtain the nano alumina seed crystals. The power of the third ultrasonic dispersion is 300W~500W; the time of the third ultrasonic dispersion is 30min~40min; the rotation speed of the first centrifugation treatment is 10000rpm~15000rpm; the time of the first centrifugation treatment is 15min~30min; and the nano alumina seed crystal is an α-Al2O3 transparent hydrosol seed crystal with a solid content of 5%~10% and an average particle size of 5nm~20nm.

[0042] As an optional implementation, in this embodiment of the application, in order to form a stable oil-in-water microemulsion system, the preparation method of the microemulsion includes the following steps: A mixture is obtained by mixing a composite surfactant, cyclohexane, and a second ammonia solution. The mixture is ultrasonically emulsified, and then a co-surfactant is added and mixed to obtain the microemulsion.

[0043] As an optional implementation, in this embodiment, the co-surfactant includes polyethylene glycol 400, and the mass ratio of the co-surfactant to the cyclohexane is (1~3) g:100 mL. Exemplary examples include a mass ratio of 1:100, 2:100, or 3:100 for the co-surfactant to the cyclohexane.

[0044] As an optional implementation, in this embodiment of the application, the composite surfactant includes sorbitan monooleate (Span80) and polyoxyethylene sorbitan monooleate (Tween80). The mass ratio of the dehydrated sorbitan monooleate to the polyoxyethylene dehydrated sorbitan monooleate is (3~5):1; the mass ratio of the composite surfactant to the cyclohexane is (5~12) g:100 mL; the concentration of the second ammonia is 0.0455 mol / L~0.4286 mol / L; the total volume ratio of the composite surfactant and the second ammonia to the volume ratio of the cyclohexane is 1:(8~15).

[0045] As an optional implementation, in this embodiment of the application, the ultrasonic emulsification temperature is 30℃~40℃, the ultrasonic emulsification time is 10min~30min, the ultrasonic emulsification power is 200W~400W, and the ultrasonic emulsification frequency is 40kHz. The average particle size of the micro-water nuclei in the microemulsion is controlled to be 10 nm to 20 nm by online monitoring of dynamic light scattering; the average particle size of the micro-water nuclei in the microemulsion is preferably 12 nm to 18 nm.

[0046] The mechanism of the microemulsion confinement effect is as follows: the micro-water nuclei formed within the microemulsion system act as nanoreactors, confining the aluminum alkoxide hydrolysis reaction within a nanoscale confined space. Within a single micro-water nucleus system, an aluminum source (aluminum alkoxide solution), ammonia catalyst, and nano-alumina seeds (seed solution) coexist. After aluminum alkoxide hydrolysis generates boehmite particles, these particles are coated with surfactant molecules, effectively inhibiting particle collisions, aggregation, and coalescence. The micro-water nucleus particle size directly limits the nucleation and growth space of the boehmite precursor. When the micro-water nucleus size is controlled within 10 nm to 20 nm, highly uniform nano-boehmite precursors can be prepared, which is a crucial prerequisite for obtaining the subsequent monodisperse final product.

[0047] As an optional implementation, in this embodiment of the application, the first mixing method includes the following steps: simultaneously pumping the aluminum alkoxide solution and the seed crystal solution into the microemulsion through a dual-channel microreactor; The inner diameter of the dual-channel microreactor is 0.5 mm to 2.0 mm. The volumetric flow rate ratio of the aluminum alkoxide solution to the seed crystal solution is 1:(1.2~2.0); The flow rates of the aluminum alkoxide solution and the seed crystal solution are controlled such that the residence time of the aluminum alkoxide solution in the dual-channel microreactor during the controlled hydrolysis reaction is 5 min to 15 min; the residence time of the seed crystal solution in the dual-channel microreactor during the controlled hydrolysis reaction is 5 min to 15 min.

[0048] As an optional implementation, in this embodiment of the application, the pH value of the controllable hydrolysis reaction is 8.5~10.5; Preferably, the pH value of the controllable hydrolysis reaction is 8.5~9.5.

[0049] Therefore, adjusting the pH of the controlled hydrolysis reaction to 8.5-10.5 is to ensure a constant hydrolysis rate and uniform product particle size. However, if the pH of the controlled hydrolysis reaction is greater than 10.5, it will cause rapid particle agglomeration and abnormal growth, and will also easily cause morphological distortion and widening of precursor particles, severely damaging the monodispersity of the product. If the pH of the controlled hydrolysis reaction is less than 8.5, it will lead to insufficient nucleation and delayed crystal growth, and will easily produce a small number of large particles and incompletely hydrolyzed impurities, resulting in uneven precursor composition, increased particle size difference, and a significant reduction in the purity and monodispersity of the final alumina powder.

[0050] In this embodiment of the application, the pH value of the controllable hydrolysis reaction is adjusted by adjusting the feed flow rate of the seed solution.

[0051] In this embodiment, the temperature of the controllable hydrolysis reaction is 40℃~60℃; the time of the controllable hydrolysis reaction is 1h~3h; the controllable hydrolysis reaction is carried out under stirring, and the stirring rate of the stirring state is 300rpm~800rpm.

[0052] In the embodiments of this application, the isolating phase includes ammonium sulfate; the molar ratio of the isolating phase to aluminum ions in the aluminum alkoxide solution is (15~30):1.

[0053] As an optional implementation, in this embodiment of the application, the stirring rate of the centrifugal demulsification process is 3000 rpm to 5000 rpm; the centrifugal demulsification process time is 5 min to 10 min.

[0054] As an optional implementation, in this embodiment of the application, in step five, the reagent for the first washing treatment includes deionized water, and the first washing treatment is performed 2 to 3 times.

[0055] As an optional implementation, in this embodiment of the application, the inlet temperature of the spray dryer is 180℃~220℃, and the outlet temperature of the spray dryer is 80℃~100℃; Thus, through spray drying, ammonium sulfate in the system can achieve molecular-level uniform compounding with boehmite precursor, maintaining the excellent monodispersity characteristics of precursor particles throughout the process.

[0056] As an optional implementation, in this embodiment of the application, in step six, the atmosphere of the gradient calcination treatment includes either an air atmosphere or an oxygen atmosphere.

[0057] As an optional implementation, in this embodiment of the application, the gradient calcination treatment includes: placing the precursor composite powder in a high-purity alumina crucible and sequentially performing a first calcination, a second calcination, and a third calcination; The heating rate of the first calcination is 2℃ / min~5℃ / min; the calcination temperature of the first calcination is 400℃~500℃; the calcination time of the first calcination is 1h~2h; after this step, organic matter and residual alcohol in the system can be removed. The heating rate of the second calcination is 3℃ / min~5℃ / min; the calcination temperature of the second calcination is 800℃~900℃; the calcination time of the second calcination is 1h~2h; after this step, boehmite is dehydrated and transformed into transition phase alumina; at the same time, ammonium sulfate in the system is heated and melted, forming a continuous liquid isolation film layer on the surface of the powder particles; The heating rate of the third calcination is 6℃ / min~7℃ / min; the calcination temperature of the third calcination is 1080℃~1120℃; the calcination time of the third calcination is 2.5h~3.5h; after this step, under the protective effect of the molten salt isolation layer and the synergistic effect of the induction of ultrafine crystal seeds, the material can directionally complete the crystal phase transformation to α-Al2O3.

[0058] However, if the calcination temperature of the second calcination is below 800℃, ammonium sulfate cannot fully melt and cannot form a continuous protective liquid film; if the calcination temperature of the third calcination is above 1120℃, the viscosity of the molten salt film decreases significantly and volatilization loss intensifies, resulting in a significant weakening of the particle isolation and protection effect. Controlling the calcination temperature of the third calcination within the temperature range of 1080℃~1120℃ can achieve the optimal synergistic match between the molten salt film's isolation and anti-agglomeration effects and the efficient α-phase transformation induced by ultrafine crystal seeds.

[0059] Furthermore, thanks to the efficient phase transformation mechanism induced by ultrafine seed crystals, the calcination temperature required for alumina to completely transform into the α phase is significantly reduced from over 1200℃ in the traditional process to 1080℃~1120℃. The high-temperature holding time is also significantly shortened, which fundamentally inhibits abnormal coarsening and growth of grains during the calcination process, ultimately producing alumina powder with uniform particle size and excellent dispersibility (i.e., high-purity nano-monodispersed alumina intermediate).

[0060] As an optional implementation, in this embodiment of the application, step seven, the purification process includes the following steps: The high-purity nano-monodisperse alumina intermediate is subjected to a second washing treatment and an acid washing treatment to obtain a second solid phase and a second liquid phase. The second solid phase is subjected to a second centrifugation treatment and a second acid washing treatment to obtain a third solid phase and a third liquid phase; this can remove the water-soluble ammonium sulfate segregating phase from the material. The third solid phase was freeze-dried to obtain the high-purity nano-monodisperse alumina.

[0061] The acid washing treatment reagents for both the first and second acid washing treatments include an acid solution; the acid solution includes either dilute nitric acid or dilute hydrochloric acid; the pH value of the acid solution is 3-4; and the acid washing treatment time is 10-30 minutes. The reagent for the second washing treatment includes deionized water, and the second washing treatment is performed 3 to 5 times; In this way, trace metal impurities, such as Fe, Ca, and Mg, that may be adsorbed on the particle surface can be further removed.

[0062] The stirring rate of the second centrifugation treatment is 3000 rpm to 6000 rpm; the time of the second centrifugation treatment is 5 min to 10 min; the temperature of the freeze-drying treatment is -50℃ to -40℃; the vacuum degree of the freeze-drying treatment is ≤10 Pa; and the time of the freeze-drying treatment is 24 h to 48 h.

[0063] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If no corresponding national standard exists, then generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer are followed.

[0064] Example 1 Example 1 provides a method for preparing high-purity nano-monodisperse alumina, comprising the following steps: Step 1: Provide aluminum alkoxide solution, seed crystal solution, and microemulsion; The preparation method of aluminum alkoxide solution includes the following steps: (1) Mix aluminum shavings with a purity of 99.9995% with an excess of isopropanol, and then perform reflux reaction and vacuum distillation in sequence to obtain aluminum isopropoxide; The reflux reaction was carried out under the action of aluminum isopropoxide catalyst; the reflux reaction time was 24 hours. The vacuum degree of the vacuum distillation process is 80 Pa; the fraction collected at 138℃ during the vacuum distillation process is used as aluminum isopropoxide; the purity of aluminum isopropoxide is ≥99.999%; (2) 100g of aluminum isopropoxide was dissolved in anhydrous isopropanol and mixed to obtain an aluminum alkoxide solution with an aluminum ion concentration of 0.1mol / L. ICP-MS analysis showed that the total amount of Fe, Na, Si, Ca, Mg, Cu, Ti, Cr, Mn and Zn in the aluminum alkoxide solution was 8ppm by mass percentage. The seed solution is an ammonia solution containing nano-alumina seeds; The preparation method of ammonia solution containing nano-alumina seeds includes the following steps: mixing nano-alumina seeds with ammonia water to obtain an ammonia solution containing nano-alumina seeds; The concentration of ammonia water is 1.0 mol / L; the nano-alumina seed crystals are α-Al2O3 transparent hydrosols with an average particle size of 12 nm; the mass ratio of Al2O3 in the nano-alumina seed crystals to the ammonia water solution containing the nano-alumina seed crystals is 1.2:100.

[0065] Transmission electron microscopy (TEM) morphology of α-Al₂O₃ transparent hydrosols with average particle sizes of 5 nm to 20 nm is shown below. Figure 1 As shown.

[0066] The preparation method of nano-alumina seeds includes the following steps: 1) Boehmite, polyethylene glycol and deionized water were mixed at a mass ratio of 1:0.01:40 and subjected to first ultrasonic dispersion and hydrothermal treatment in sequence to obtain boehmite nanosheet precursor. The first ultrasonic dispersion time was 35 min, and the power of the first ultrasonic dispersion was 400 W; the hydrothermal treatment temperature was 190℃; the hydrothermal treatment time was 24 h, and the filling degree of the hot reactor used for hydrothermal treatment was 78%; 2) The boehmite nanosheet precursor was subjected to centrifugal washing and freeze-drying treatment in sequence to obtain fluffy boehmite powder; The centrifugal washing process was carried out at a speed of 10,000 rpm; the freeze-drying process was carried out at a temperature of 40°C; and the freeze-drying process was carried out for 36 hours. 3) Boehmite powder and ammonium sulfate were mixed at a mass ratio of 10:3 and calcined in air to obtain nano-alumina seed intermediates. The calcination process involved a heating rate of 5℃ / min, a calcination temperature of 1000℃, a calcination time of 2h, and a primary particle size of 30nm~60nm for the nano-alumina seed intermediate. 4) The nano-alumina seed intermediate is subjected to a fourth washing treatment to obtain a pure nano-alumina seed intermediate; The fourth washing process involves washing with deionized water four times. 5) The pure nano-alumina seed intermediate, sodium hexametaphosphate, and solvent are mixed and then subjected to a second ultrasonic dispersion and ball milling process to obtain a dispersion slurry. Solvent 1 includes deionized water; the mass ratio of sodium hexametaphosphate, α-Al2O3 in the pure nano-alumina seed intermediate, and solvent 2 is 1:50:190; the power of the second ultrasonic dispersion is 400W; the time of the second ultrasonic dispersion is 2h; the grinding media for ball milling includes zirconia balls, the ball-to-material ratio for ball milling is 6:1, the dispersion media for ball milling includes ethanol, the ball milling speed for ball milling is 300rpm, and the ball milling time for ball milling is 10h; 6) Mix the dispersion slurry with deionized water at a mass ratio of 1:10, and perform a third ultrasonic dispersion and a first centrifugation treatment in sequence. Take the supernatant to obtain nano-alumina seed crystals.

[0067] The power of the third ultrasonic dispersion was 450W; the time of the third ultrasonic dispersion was 30min; the rotation speed of the first centrifugation treatment was 12000rpm; the time of the first centrifugation treatment was 30min; and the nano alumina seed crystals were α-Al2O3 transparent hydrosol seed crystals with a solid content of 8% and an average particle size of 12nm.

[0068] The preparation method of microemulsion includes the following steps: (1) Mix 24g of composite surfactant, 300mL of cyclohexane and second ammonia water to obtain a mixture; The composite surfactant consists of 18g of sorbitan monooleate (Span80) and 6g of polyoxyethylene sorbitan monooleate (Tween80), with a mass ratio of sorbitan monooleate to polyoxyethylene sorbitan monooleate of 3:1; the mass ratio of the composite surfactant to cyclohexane is 8g:100mL; and the second ammonia solution is a mixture of 30mL of deionized water and 5mL of dilute ammonia solution with a concentration of 0.8mol / L.

[0069] (2) The mixture was ultrasonically emulsified, and then 3g of polyethylene glycol 400 was added to obtain a microemulsion; The ultrasonic emulsification temperature was 35℃, the ultrasonic emulsification time was 20 min, the ultrasonic emulsification power was 300 W, and the ultrasonic emulsification frequency was 40 kHz. The average particle size of the micro water nuclei in the microemulsion was 15 nm as determined by DLS.

[0070] Step 2: The aluminum alkoxide solution, seed crystal solution, and microemulsion are mixed to obtain a composite phase mixture; The first mixing method includes the following steps: simultaneously pumping aluminum alkoxide solution and seed crystal solution into the microemulsion through a dual-channel microreactor; the inner diameter of the dual-channel microreactor is 1.0 mm; The flow rate of the aluminum alkoxide solution was 5 mL / min, and the flow rate of the seed crystal solution was 7 mL / min; the volumetric flow rate ratio of the aluminum alkoxide solution to the seed crystal solution was 1:1.4. The residence time of the aluminum alkoxide solution in the dual-channel microreactor for controlled hydrolysis was 15 min; the residence time of the seed crystal solution in the dual-channel microreactor for controlled hydrolysis was 10 min.

[0071] Step 3: Perform a controlled hydrolysis reaction on the intermediate of the composite phase mixture to obtain a hydrolyzed mixture; mix the hydrolyzed mixture with the separating phase evenly (stir for 45 min) to obtain a composite phase mixture; The pH value of the controlled hydrolysis reaction is 9.2; the pH value of the controlled hydrolysis reaction is adjusted by: adjusting the feed flow rate of the seed crystal solution; the temperature of the controlled hydrolysis reaction is 50℃; the time of the controlled hydrolysis reaction is 2h; the controlled hydrolysis reaction is carried out under stirring, and the stirring speed is 500rpm. The isolating phase is 135g of ammonium sulfate, and the molar ratio of ammonium sulfate to aluminum ions in the aluminum alkoxide solution is approximately 22:1.

[0072] Step 4: Centrifuge the composite phase mixture to demulsify it, and obtain the first solid phase, the first liquid phase, and the oil phase. The stirring rate for centrifugal demulsification was 4000 rpm; the centrifugal demulsification time was 10 min. Step 5: The first solid phase is subjected to a first washing treatment and a spray drying treatment in sequence to obtain the precursor composite powder; The first washing process involves washing three times with deionized water; the inlet temperature of the spray dryer is 200℃, and the outlet temperature of the spray dryer is 90℃. Step 6: Under an air atmosphere with a flow rate of 100 mL / min, the precursor composite powder is subjected to gradient calcination and cooled to room temperature to obtain a high-purity nano-monodisperse alumina intermediate. The gradient calcination process includes sequentially performing a first calcination, a second calcination, and a third calcination on the precursor composite powder. The heating rate for the first calcination is 3℃ / min; the calcination temperature for the first calcination is 450℃; the calcination time for the first calcination is 1.5h; the heating rate for the second calcination is 4℃ / min; the calcination temperature for the second calcination is 850℃; the calcination time for the second calcination is 1.5h; the heating rate for the third calcination is 6.5℃ / min; the calcination temperature for the third calcination is 1100℃; the calcination time for the third calcination is 3h. Step 7: Purify the high-purity nano-monodisperse alumina intermediate to obtain white high-purity nano-monodisperse alumina. The purification process includes the following steps: subjecting the high-purity nano-monodisperse alumina intermediate to a second washing treatment and an acid washing treatment to obtain a second solid phase and a second liquid phase; The second solid phase is subjected to a second centrifugation treatment and a second acid washing treatment to obtain a third solid phase and a third liquid phase; The third solid phase was freeze-dried to obtain high-purity nano-monodisperse alumina.

[0073] The second washing process involved washing with deionized water four times; the second centrifugation process involved stirring at 4000 rpm for 8 minutes; both the first and second acid washing processes used dilute hydrochloric acid with a pH of 4 for 20 minutes each; the freeze-drying process was carried out at -45°C with a vacuum of 5 Pa for 18 hours.

[0074] The high-purity nano-monodisperse alumina prepared by the above method was analyzed by field emission electron microscopy (FE-SEM), and the results are as follows: Figure 2 As shown: the product particles are spherical with clear boundaries between particles and no obvious sintered agglomerates.

[0075] Characterization: ICP-OES analysis showed that the purity of the high-purity nano-monodisperse alumina was 99.992%. XRD analysis showed that the high-purity nano-monodisperse alumina was a pure α-Al2O3 phase; By mass percentage, the α-Al₂O₃ phase of high-purity nano-monodisperse alumina is ≥98%; the α-phase conversion rate is 99.8%. By mass percentage, the high-purity nano-monodisperse alumina contains 42 ppm Na2O, 25 ppm Fe2O3, and 38 ppm SiO2. FE-SEM testing showed that the average particle size of the primary particles of high-purity nano-monodisperse alumina was 30 nm. Laser particle size analysis showed that the secondary particles D of high-purity nano-monodisperse alumina... 50 The particle size is 75nm, D 10=48nm, D 90 =102nm, the particle size distribution ratio D of secondary particles 90 / D 10 =2.12; Particle size distribution dispersion index (PDI) of high-purity nano-monodisperse alumina is 0.079; The specific surface area of ​​high-purity nano-monodisperse alumina, measured by the BET method, is 42 m². 2 ·g -1 .

[0076] Example 2 Example 2 provides a method for preparing high-purity nano-monodisperse alumina, comprising the following steps: Step 1: Provide an aluminum alkoxide solution with an aluminum ion concentration of 0.2 mol / L, a seed crystal solution, and a microemulsion; The preparation method of aluminum alkoxide solution is the same as in Example 1, and will not be repeated here.

[0077] The seed solution is an ammonia solution containing nano-alumina seeds; The preparation method of ammonia solution containing nano-alumina seeds includes the following steps: mixing nano-alumina seeds with ammonia water to obtain an ammonia solution containing nano-alumina seeds; The concentration of ammonia water is 1.8 mol / L; the nano-alumina seed crystals are α-Al2O3 transparent hydrosols with an average particle size of 12 nm; the mass ratio of Al2O3 in the nano-alumina seed crystals to the ammonia water solution containing the nano-alumina seed crystals is 1:40.

[0078] The preparation method of nano-alumina seeds includes the following steps: 1) Boehmite, polyethylene glycol and deionized water were mixed at a mass ratio of 1:0.01:40 and subjected to first ultrasonic dispersion and hydrothermal treatment in sequence to obtain boehmite nanosheet precursor. The first ultrasonic dispersion time was 35 min, and the power of the first ultrasonic dispersion was 300 W; the hydrothermal treatment temperature was 200℃; the hydrothermal treatment time was 23 h, and the filling degree of the hot reactor used for hydrothermal treatment was 80%. 2) The boehmite nanosheet precursor was subjected to centrifugal washing and freeze-drying treatment in sequence to obtain fluffy boehmite powder; The centrifugal washing process was carried out at a speed of 10,000 rpm; the freeze-drying process was carried out at a temperature of 40°C; and the freeze-drying process was carried out for 36 hours. 3) Boehmite powder and ammonium sulfate were mixed at a mass ratio of 10:4 and calcined in air to obtain nano-alumina seed intermediates. The calcination process involved a heating rate of 5℃ / min, a calcination temperature of 1000℃, a calcination time of 2h, and a primary particle size of 30nm~60nm for the nano-alumina seed intermediate. 4) The nano-alumina seed intermediate is subjected to a fourth washing treatment to obtain a pure nano-alumina seed intermediate; The fourth washing process involves washing three times with deionized water. 5) The pure nano-alumina seed intermediate, sodium hexametaphosphate, and solvent are mixed and then subjected to a second ultrasonic dispersion and ball milling process to obtain a dispersion slurry. Solvent 1 includes deionized water; the mass ratio of sodium hexametaphosphate, α-Al2O3 in the pure nano-alumina seed intermediate, and solvent 2 is 1:50:200; the power of the second ultrasonic dispersion is 400W; the time of the second ultrasonic dispersion is 2h; the grinding media for ball milling includes zirconia balls, the ball-to-material ratio for ball milling is 8:1, the dispersion media for ball milling includes ethanol, the ball milling speed for ball milling is 400rpm, and the ball milling time for ball milling is 10h; 6) Mix the dispersion slurry with deionized water at a mass ratio of 1:9, and perform a third ultrasonic dispersion and a first centrifugation treatment in sequence. Take the supernatant to obtain nano-alumina seed crystals.

[0079] The third ultrasonic dispersion power was 400W; the third ultrasonic dispersion time was 30min; the first centrifugation speed was 10000rpm; the first centrifugation time was 30min; and the nano alumina seed crystals were α-Al2O3 transparent hydrosol seed crystals with a solid content of 8% and an average particle size of 12nm.

[0080] The preparation method of microemulsion includes the following steps: (1) Mix 36g of composite surfactant, 300mL of cyclohexane and second ammonia water to obtain a mixture; The composite surfactant consists of 27g of sorbitan monooleate and 9g of polyoxyethylene sorbitan monooleate, with a mass ratio of 3:1 between the two. The mass ratio of the composite surfactant to cyclohexane is 12g:100mL. The second ammonia solution is a mixture of 20mL of deionized water and 8mL of dilute ammonia solution with a concentration of 1.5mol / L.

[0081] (2) The mixture was ultrasonically emulsified, and then 4g of polyethylene glycol 400 was added to obtain a microemulsion; The ultrasonic emulsification temperature was 35℃, the ultrasonic emulsification time was 25 min, the ultrasonic emulsification power was 350 W, and the ultrasonic emulsification frequency was 40 kHz. The average particle size of the micro water nuclei in the microemulsion was 20 nm as determined by DLS.

[0082] Step 2: The aluminum alkoxide solution, seed crystal solution, and microemulsion are mixed to obtain a composite phase mixture; The first mixing method includes the following steps: aluminum alkoxide solution and seed crystal solution are simultaneously pumped into the microemulsion through a dual-channel microreactor; the inner diameter of the dual-channel microreactor is 2.0 mm; The flow rate of the aluminum alkoxide solution was 8 mL / min, and the flow rate of the seed crystal solution was 14 mL / min; the volumetric flow rate ratio of the aluminum alkoxide solution to the seed crystal solution was 1:1.75. The residence time of the aluminum alkoxide solution in the dual-channel microreactor during the controlled hydrolysis reaction was 15 min; the residence time of the seed crystal solution in the dual-channel microreactor during the controlled hydrolysis reaction was also 15 min.

[0083] Step 3: Perform a controlled hydrolysis reaction on the intermediate of the composite phase mixture to obtain a hydrolyzed mixture; mix the hydrolyzed mixture with the separating phase evenly (stir for 60 min) to obtain a composite phase mixture; The pH value of the controlled hydrolysis reaction is in the range of 8.9~9.5; the pH value of the controlled hydrolysis reaction is adjusted by: adjusting the feed flow rate of the seed crystal solution; the temperature of the controlled hydrolysis reaction is 60℃; the time of the controlled hydrolysis reaction is 3h; the controlled hydrolysis reaction is carried out under stirring, and the stirring speed is 800rpm. The isolating phase is 360g of ammonium sulfate, and the molar ratio of ammonium sulfate to aluminum ions in the aluminum alkoxide solution is approximately 30:1.

[0084] Step 4: Centrifuge the composite phase mixture to demulsify it, and obtain the first solid phase, the first liquid phase, and the oil phase. The stirring rate for centrifugal demulsification was 4000 rpm; the centrifugal demulsification time was 10 min. Step 5: The first solid phase is subjected to a first washing treatment and a spray drying treatment in sequence to obtain the precursor composite powder; The first washing process involves washing three times with deionized water; the inlet temperature of the spray dryer is 220℃, and the outlet temperature of the spray dryer is 100℃. Step 6: Under an air atmosphere with a flow rate of 100 mL / min, the precursor composite powder is subjected to gradient calcination to obtain a high-purity nano-monodisperse alumina intermediate. The gradient calcination process includes sequentially performing a first calcination, a second calcination, and a third calcination on the precursor composite powder. The heating rate for the first calcination is 5℃ / min; the calcination temperature for the first calcination is 500℃; the calcination time for the first calcination is 2h; the heating rate for the second calcination is 5℃ / min; the calcination temperature for the second calcination is 900℃; the calcination time for the second calcination is 2h; the heating rate for the third calcination is 7℃ / min; the calcination temperature for the third calcination is 1120℃; the calcination time for the third calcination is 3.5h; Step 7: Purify the high-purity nano-monodisperse alumina intermediate to obtain white high-purity nano-monodisperse alumina.

[0085] The purification process includes the following steps: performing a second washing treatment and an acid washing treatment on the high-purity nano-monodisperse alumina intermediate to obtain a second solid phase and a second liquid phase; performing a second centrifugation treatment and an acid washing treatment on the second solid phase to obtain a third solid phase and a third liquid phase; and performing freeze-drying treatment on the third solid phase to obtain high-purity nano-monodisperse alumina.

[0086] The second washing process involved washing with deionized water five times; the second centrifugation process involved stirring at 6000 rpm and centrifuging for 10 minutes; both the first and second acid washing processes used dilute hydrochloric acid with a pH of 4 and lasted for 20 minutes; the freeze-drying process was carried out at a temperature of -40°C, a vacuum of 5 Pa, and for 24 hours. The high-purity nano-monodisperse alumina was prepared by the above method; Characterization: ICP-OES analysis showed that the purity of the high-purity nano-monodisperse alumina was 99.991%. XRD analysis showed that the high-purity nano-monodisperse alumina was a pure α-Al2O3 phase; By mass percentage, the high-purity nano-monodisperse alumina contains ≥98% α-Al₂O₃ phase and has an α-phase conversion rate of 98.2%. By mass percentage, the high-purity nano-monodisperse alumina contains 48 ppm Na2O, 28 ppm Fe2O3, and 45 ppm SiO2. FE-SEM testing showed that the average particle size of the primary particles of high-purity nano-monodisperse alumina was 45 nm. Laser particle size analysis showed that the secondary particles D of high-purity nano-monodisperse alumina... 50 Particle size is 85nm; D 10 =51nm, D 90 =118nm, the particle size distribution ratio D of secondary particles 90 / D 10 The ratio is 2.31; the particle size distribution dispersion index (PDI) of high-purity nano-monodisperse alumina is 0.095. The specific surface area of ​​high-purity nano-monodisperse alumina, measured by the BET method, is 35 m². 2 ·g -1 .

[0087] This embodiment corresponds to the upper limit values ​​of aluminum ion concentration, oil-water volume ratio, surfactant content, micro-water core particle size, ammonium sulfate molar ratio, and calcination temperature of stepped calcination in claim 1, verifying the feasibility of the high end of the scope of the claim.

[0088] Example 3 Example 3 provides a method for preparing high-purity nano-monodisperse alumina, comprising the following steps: Step 1: Provide an aluminum alkoxide solution, a seed crystal solution, and a microemulsion with an aluminum ion concentration of 0.05 mol / L; The preparation method of aluminum alkoxide solution is the same as in Example 1, and will not be repeated here.

[0089] The seed solution is an ammonia solution containing nano-alumina seeds; The preparation method of ammonia solution containing nano-alumina seeds includes the following steps: mixing nano-alumina seeds with ammonia water to obtain an ammonia solution containing nano-alumina seeds; The concentration of ammonia water is 1.5 mol / L; the nano-alumina seed crystals are α-Al2O3 transparent hydrosols with an average particle size of 5 nm to 20 nm; the mass ratio of Al2O3 in the nano-alumina seed crystals to the ammonia water solution containing the nano-alumina seed crystals is 1.5:100.

[0090] The preparation method of nano-alumina seeds includes the following steps: 1) Boehmite, polyethylene glycol and deionized water were mixed at a mass ratio of 1:0.01:40 and subjected to first ultrasonic dispersion and hydrothermal treatment in sequence to obtain boehmite nanosheet precursor. The first ultrasonic dispersion time was 35 min, and the power of the first ultrasonic dispersion was 400 W; the hydrothermal treatment temperature was 200℃; the hydrothermal treatment time was 24 h, and the filling degree of the hot reactor used for hydrothermal treatment was 75%; 2) The boehmite nanosheet precursor was subjected to centrifugal washing and freeze-drying treatment in sequence to obtain fluffy boehmite powder; The centrifugal washing process was carried out at a speed of 10,000 rpm; the freeze-drying process was carried out at a temperature of 40°C; and the freeze-drying process was carried out for 36 hours. 3) Boehmite powder and ammonium sulfate were mixed at a mass ratio of 10:3 and calcined in air to obtain nano-alumina seed intermediates. The calcination process involved a heating rate of 5℃ / min, a calcination temperature of 1000℃, a calcination time of 2h, and a primary particle size of 30nm~60nm for the nano-alumina seed intermediate. 4) The nano-alumina seed intermediate is subjected to a fourth washing treatment to obtain a pure nano-alumina seed intermediate; The fourth washing process involves washing three times with deionized water. 5) The pure nano-alumina seed intermediate, sodium hexametaphosphate, and solvent are mixed and then subjected to a second ultrasonic dispersion and ball milling process to obtain a dispersion slurry. Solvent one includes deionized water; the mass ratio of sodium hexametaphosphate, α-Al2O3 in the pure nano-alumina seed intermediate, and solvent two is 1:50:225; the power of the second ultrasonic dispersion is 400W; the time of the second ultrasonic dispersion is 2h; the grinding medium for ball milling includes zirconia balls, the ball-to-material ratio for ball milling is 6:1, the dispersion medium for ball milling includes ethanol, the ball milling speed for ball milling is 400rpm, and the ball milling time for ball milling is 10h; 6) Mix the dispersion slurry with deionized water at a mass ratio of 1:11, and then perform a third ultrasonic dispersion and a first centrifugation treatment in sequence. Take the supernatant to obtain nano-alumina seed crystals.

[0091] The power of the third ultrasonic dispersion was 400W; the time of the third ultrasonic dispersion was 30min; the speed of the first centrifugation treatment was 12000rpm; the time of the first centrifugation treatment was 30min; and the nano alumina seed crystals were α-Al2O3 transparent hydrosol seed crystals with a solid content of 8% and an average particle size of 5nm~20nm.

[0092] The preparation method of microemulsion includes the following steps: (1) Mix 16g of composite surfactant, 320mL of cyclohexane and second ammonia water to obtain a mixture; The composite surfactant consists of 12g of sorbitan monooleate and 4g of polyoxyethylene sorbitan monooleate, with a mass ratio of 3:1 between the two. The mass ratio of the composite surfactant to cyclohexane is 5:100. The second ammonia solution is a mixture of 40mL of deionized water and 4mL of 0.5mol / L dilute ammonia solution.

[0093] (2) The mixture was ultrasonically emulsified, and then 4g of polyethylene glycol 400 was added to obtain a microemulsion; The ultrasonic emulsification temperature was 30℃, the ultrasonic emulsification time was 10 min, the ultrasonic emulsification power was 200 W, and the ultrasonic emulsification frequency was 40 kHz. The average particle size of the micro water nuclei in the microemulsion was 10 nm as determined by DLS.

[0094] Step 2: The aluminum alkoxide solution, seed crystal solution, and microemulsion are mixed to obtain a composite phase mixture; The first mixing method includes the following steps: aluminum alkoxide solution and seed crystal solution are simultaneously pumped into the microemulsion through a dual-channel microreactor; the inner diameter of the dual-channel microreactor is 0.5 mm; The flow rate of the aluminum alkoxide solution was 2 mL / min, and the flow rate of the seed crystal solution was 3 mL / min; the volumetric flow rate ratio of the aluminum alkoxide solution to the seed crystal solution was 1:1.5. The residence time of the aluminum alkoxide solution in the dual-channel microreactor during the controlled hydrolysis reaction was 10 min; the residence time of the seed crystal solution in the dual-channel microreactor during the controlled hydrolysis reaction was also 10 min.

[0095] Step 3: Perform a controlled hydrolysis reaction on the intermediate of the composite phase mixture to obtain a hydrolyzed mixture; mix the hydrolyzed mixture with the separating phase evenly (stir for 30 min) to obtain a composite phase mixture; The pH value of the controlled hydrolysis reaction is 8.5~9.1; the pH value of the controlled hydrolysis reaction is adjusted by: adjusting the feed flow rate of the seed crystal solution; the temperature of the controlled hydrolysis reaction is 40℃; the time of the controlled hydrolysis reaction is 1h; the controlled hydrolysis reaction is carried out under stirring, and the stirring speed is 300rpm. The isolating phase is 45g of ammonium sulfate, and the molar ratio of ammonium sulfate to aluminum ions in the aluminum alkoxide solution is approximately 15:1.

[0096] Step 4: Centrifuge the composite phase mixture to demulsify it, and obtain the first solid phase, the first liquid phase, and the oil phase. The stirring rate for centrifugal demulsification was 5000 rpm; the centrifugal demulsification time was 10 min. Step 5: The first solid phase is subjected to a first washing treatment and a spray drying treatment in sequence to obtain the precursor composite powder; The first washing process involves washing three times with deionized water; the inlet temperature of the spray dryer is 180℃, and the outlet temperature of the spray dryer is 80℃. Step 6: Under an air atmosphere with a flow rate of 100 mL / min, the precursor composite powder is subjected to gradient calcination to obtain a high-purity nano-monodisperse alumina intermediate. The gradient calcination process includes sequentially performing a first calcination, a second calcination, and a third calcination on the precursor composite powder. The heating rate for the first calcination is 2℃ / min; the calcination temperature for the first calcination is 400℃; the calcination time for the first calcination is 1h; the heating rate for the second calcination is 3℃ / min; the calcination temperature for the second calcination is 800℃; the calcination time for the second calcination is 1h; the heating rate for the third calcination is 6℃ / min; the calcination temperature for the third calcination is 1080℃; the calcination time for the third calcination is 2.5h; Step 7: Purify the high-purity nano-monodisperse alumina intermediate to obtain high-purity nano-monodisperse alumina.

[0097] The purification process includes the following steps: performing a second washing treatment and an acid washing treatment on the high-purity nano-monodisperse alumina intermediate to obtain a second solid phase and a second liquid phase; performing a second centrifugation treatment and an acid washing treatment on the second solid phase to obtain a third solid phase and a third liquid phase; and performing freeze-drying treatment on the third solid phase to obtain high-purity nano-monodisperse alumina.

[0098] The second washing process involved washing three times with deionized water; the second centrifugation process involved stirring at 3000 rpm for 5 minutes; both the first and second acid washing processes used dilute hydrochloric acid with a pH of 4 for 20 minutes each; the freeze-drying process was carried out at -50°C with a vacuum of 5 Pa for 12 hours.

[0099] The high-purity nano-monodisperse alumina was prepared by the above method; Characterization: ICP-OES analysis showed that the purity of the high-purity nano-monodisperse alumina was 99.994%. XRD analysis showed that the high-purity nano-monodisperse alumina was a pure α-Al2O3 phase; By mass percentage, the high-purity nano-monodisperse alumina contains ≥98% α-Al₂O₃ phase and has an α-phase conversion rate of 99.3%. By mass percentage, the high-purity nano-monodisperse alumina contains 35 ppm Na2O, 18 ppm Fe2O3, and 28 ppm SiO2.

[0100] FE-SEM testing showed that the average particle size of the primary particles of high-purity nano-monodisperse alumina was 22 nm. Laser particle size analysis showed that the secondary particles D of high-purity nano-monodisperse alumina... 50 The particle size is 55nm, D 10 =36nm, D 90 =74nm; the particle size distribution ratio D of secondary particles 90 / D 10The ratio is 2.06; the particle size distribution dispersion index (PDI) of high-purity nano-monodisperse alumina is 0.072. The specific surface area of ​​high-purity nano-monodisperse alumina, measured by the BET method, is 58 m². 2 ·g -1 .

[0101] This embodiment corresponds to the lower limit values ​​of aluminum ion concentration, oil-water volume ratio, surfactant content, micro-water core particle size, ammonium sulfate molar ratio, and calcination temperature of stepped calcination in claim 1, verifying the feasibility of the lower end of the scope of the claim.

[0102] Example 4 Example 4 provides a method for preparing high-purity nano-monodisperse alumina, comprising the following steps: Step 1: Provide an aluminum alkoxide solution, a seed crystal solution, and a microemulsion with an aluminum ion concentration of 0.15 mol / L; The preparation method of aluminum alkoxide solution is the same as in Example 1, and will not be repeated here.

[0103] The seed solution is an ammonia solution containing nano-alumina seeds; The preparation method of ammonia solution containing nano-alumina seeds includes the following steps: mixing nano-alumina seeds with ammonia water to obtain an ammonia solution containing nano-alumina seeds; The concentration of ammonia water is 1.5 mol / L; the nano-alumina seed crystals are α-Al2O3 transparent hydrosols with an average particle size of 5 nm to 20 nm; the mass ratio of Al2O3 in the nano-alumina seed crystals to the ammonia water solution containing the nano-alumina seed crystals is 1.5:100.

[0104] The preparation method of nano-alumina seeds includes the following steps: 1) Boehmite, polyethylene glycol and deionized water were mixed at a mass ratio of 1:0.01:30 and subjected to first ultrasonic dispersion and hydrothermal treatment in sequence to obtain boehmite nanosheet precursor. The first ultrasonic dispersion time was 35 min, and the power of the first ultrasonic dispersion was 400 W; the hydrothermal treatment temperature was 190℃; the hydrothermal treatment time was 18 h, and the filling degree of the hot reactor used for hydrothermal treatment was 78%; 2) The boehmite nanosheet precursor was subjected to centrifugal washing and freeze-drying treatment in sequence to obtain fluffy boehmite powder; The centrifugal washing process was carried out at a speed of 10,000 rpm; the freeze-drying process was carried out at a temperature of 40°C; and the freeze-drying process was carried out for 36 hours. 3) Boehmite powder and ammonium sulfate were mixed at a mass ratio of 10:3 and calcined in air to obtain nano-alumina seed intermediates. The heating rate of the calcination treatment was 5℃ / min; the calcination temperature was 1020℃; the calcination time was 2h; and the primary particle size of the nano-alumina seed intermediate was 30nm~60nm. 4) The nano-alumina seed intermediate is subjected to a fourth washing treatment to obtain a pure nano-alumina seed intermediate; The fourth washing process involves washing with deionized water four times. 5) The pure nano-alumina seed intermediate, sodium hexametaphosphate, and solvent are mixed and then subjected to a second ultrasonic dispersion and ball milling process to obtain a dispersion slurry. Solvent one includes deionized water; the mass ratio of sodium hexametaphosphate, α-Al2O3 in the pure nano-alumina seed intermediate, and solvent two is 1:50:200; the power of the second ultrasonic dispersion is 400W; the time of the second ultrasonic dispersion is 2h; the grinding medium for ball milling includes zirconia balls, the ball-to-material ratio for ball milling is 8:1, the dispersion medium for ball milling includes ethanol, the ball milling speed for ball milling is 300rpm, and the ball milling time for ball milling is 10h; 6) Mix the dispersion slurry with deionized water at a mass ratio of 1:10, and perform a third ultrasonic dispersion and a first centrifugation treatment in sequence. Take the supernatant to obtain nano-alumina seed crystals.

[0105] The third ultrasonic dispersion power was 400W; the third ultrasonic dispersion time was 30min; the first centrifugation speed was 12000rpm; the first centrifugation time was 30min; and the nano alumina seed crystals were α-Al2O3 transparent hydrosol seed crystals with a solid content of 6% and an average particle size of 5nm~20nm.

[0106] The preparation method of microemulsion includes the following steps: (1) Mix 24g of composite surfactant, 350 mL of cyclohexane and second ammonia water to obtain a mixture; The composite surfactant consists of 20g of sorbitan monooleate and 4g of polyoxyethylene sorbitan monooleate, with a mass ratio of 5:1 between the two. The mass ratio of the composite surfactant to cyclohexane is 6.857:100. The second ammonia solution is a mixture of 29mL of deionized water and 8mL of 1.2mol / L dilute ammonia solution.

[0107] (2) The mixture was ultrasonically emulsified, and then 5g of polyethylene glycol 400 was added to obtain a microemulsion; The ultrasonic emulsification temperature was 35℃, the ultrasonic emulsification time was 25 min, the ultrasonic emulsification power was 300 W, and the ultrasonic emulsification frequency was 40 kHz. The average particle size of the micro water nuclei in the microemulsion was 12 nm, as determined by DLS.

[0108] Step 2: The aluminum alkoxide solution, seed crystal solution, and microemulsion are mixed to obtain a composite phase mixture; The first mixing method includes the following steps: aluminum alkoxide solution and seed crystal solution are simultaneously pumped into the microemulsion through a dual-channel microreactor; the inner diameter of the dual-channel microreactor is 0.8 mm; The flow rate of the aluminum alkoxide solution was 4 mL / min, and the flow rate of the seed crystal solution was 6 mL / min; the volumetric flow rate ratio of the aluminum alkoxide solution to the seed crystal solution was 1:1.5. The residence time of the aluminum alkoxide solution in the dual-channel microreactor for controlled hydrolysis was 12 min; the residence time of the seed crystal solution in the dual-channel microreactor for controlled hydrolysis was 5 min.

[0109] Step 3: Perform a controlled hydrolysis reaction on the intermediate of the composite phase mixture to obtain a hydrolyzed mixture; mix the hydrolyzed mixture with the separating phase evenly (stir for 50 min) to obtain a composite phase mixture; The pH value of the controlled hydrolysis reaction is 9.3~9.7; the pH value of the controlled hydrolysis reaction is adjusted by: adjusting the feed flow rate of the seed crystal solution; the temperature of the controlled hydrolysis reaction is 55℃; the time of the controlled hydrolysis reaction is 1.5h; the controlled hydrolysis reaction is carried out under stirring, and the stirring speed is 600rpm. The isolating phase is 180g of ammonium sulfate, and the molar ratio of ammonium sulfate to aluminum ions in the aluminum alkoxide solution is approximately 25:1.

[0110] Step 4: Centrifuge the composite phase mixture to demulsify it, and obtain the first solid phase, the first liquid phase, and the oil phase. The stirring rate for centrifugal demulsification was 4000 rpm; the centrifugal demulsification time was 10 min. Step 5: The first solid phase is subjected to a first washing treatment and a spray drying treatment in sequence to obtain the precursor composite powder; The first washing process involves washing three times with deionized water; the inlet temperature of the spray dryer is 210℃, and the outlet temperature of the spray dryer is 95℃. Step 6: Under an air atmosphere with a flow rate of 100 mL / min, the precursor composite powder is subjected to gradient calcination to obtain a high-purity nano-monodisperse alumina intermediate. The gradient calcination process includes sequentially performing a first calcination, a second calcination, and a third calcination on the precursor composite powder. The heating rate for the first calcination is 4℃ / min; the calcination temperature for the first calcination is 480℃; the calcination time for the first calcination is 1h; the heating rate for the second calcination is 5℃ / min; the calcination temperature for the second calcination is 880℃; the calcination time for the second calcination is 1h; the heating rate for the third calcination is 7℃ / min; the calcination temperature for the third calcination is 1120℃; the calcination time for the third calcination is 2.5h; Step 7: Purify the high-purity nano-monodisperse alumina intermediate to obtain high-purity nano-monodisperse alumina. The purification process includes the following steps: subjecting the high-purity nano-monodisperse alumina intermediate to a second washing treatment and an acid washing treatment to obtain a second solid phase and a second liquid phase; The second solid phase was subjected to a second centrifugation treatment and a second acid washing treatment in sequence to obtain a third solid phase and a third liquid phase; The third solid phase was freeze-dried to obtain high-purity nano-monodisperse alumina.

[0111] The second washing process involved washing with deionized water four times; the second centrifugation process involved stirring at 5000 rpm for 6 minutes; both the first and second acid washing processes used dilute nitric acid at pH 3.5 for 20 minutes each; the freeze-drying process involved freezing at 40°C with a vacuum of 5 Pa for 20 hours.

[0112] The high-purity nano-monodisperse alumina was prepared by the above method; Characterization: ICP-OES analysis showed that the purity of the high-purity nano-monodisperse alumina was 99.997%; (acid washing further reduced trace metal impurities). XRD analysis showed that the high-purity nano-monodisperse alumina was a pure α-Al2O3 phase; By mass percentage, the high-purity nano-monodisperse alumina contains ≥98% α-Al2O3 phase and has a 100% α-phase conversion rate. By mass percentage, the high-purity nano-monodisperse alumina contains 28 ppm Na2O, 12 ppm Fe2O3, 25 ppm SiO2, 8 ppm CaO, and 5 ppm MgO. FE-SEM testing showed that the average particle size of the primary particles of high-purity nano-monodisperse alumina was 28 nm. Laser particle size analysis showed that the secondary particles D of high-purity nano-monodisperse alumina... 50 The particle size is 68nm, D 10 =40nm, D 90 =95nm, the particle size distribution ratio D of secondary particles 90 / D10 The ratio is 2.38; the particle size distribution dispersion index (PDI) of high-purity nano-monodisperse alumina is 0.10. The specific surface area of ​​high-purity nano-monodisperse alumina, measured by the BET method, was 48 m². 2 ·g -1 .

[0113] Example 5 Example 5 provides a method for preparing high-purity nano-monodisperse alumina, comprising the following steps: Step 1: Provide an aluminum alkoxide solution, a seed crystal solution, and a microemulsion with an aluminum ion concentration of 0.08 mol / L; The preparation method of aluminum alkoxide solution is the same as in Example 1, and will not be repeated here.

[0114] The seed solution is an ammonia solution containing nano-alumina seeds; The preparation method of ammonia solution containing nano-alumina seeds includes the following steps: mixing nano-alumina seeds with ammonia water to obtain an ammonia solution containing nano-alumina seeds; The concentration of ammonia water is 1.2 mol / L; the nano-alumina seed crystals are α-Al2O3 transparent hydrosols with an average particle size of 5 nm to 20 nm; the mass ratio of Al2O3 in the nano-alumina seed crystals to the ammonia water solution containing the nano-alumina seed crystals is 1:50.

[0115] The preparation method of nano-alumina seeds includes the following steps: 1) Boehmite, polyethylene glycol and deionized water were mixed at a mass ratio of 1:0.01:30 and subjected to first ultrasonic dispersion and hydrothermal treatment in sequence to obtain boehmite nanosheet precursor. The first ultrasonic dispersion time was 35 min, and the power of the first ultrasonic dispersion was 400 W; the hydrothermal treatment temperature was 200℃; the hydrothermal treatment time was 24 h, and the filling degree of the hot reactor used for hydrothermal treatment was 78%; 2) The boehmite nanosheet precursor was subjected to centrifugal washing and freeze-drying treatment in sequence to obtain fluffy boehmite powder; The centrifugal washing process was carried out at a speed of 10,000 rpm; the freeze-drying process was carried out at a temperature of 40°C; and the freeze-drying process was carried out for 48 hours. 3) Boehmite powder and ammonium sulfate were mixed at a mass ratio of 10:3 and calcined in air to obtain nano-alumina seed intermediates. The heating rate of the calcination treatment was 5℃ / min; the calcination temperature was 1020℃; the calcination time was 1.5h; and the primary particle size of the nano-alumina seed intermediate was 30nm~60nm. 4) The nano-alumina seed intermediate is subjected to a fourth washing treatment to obtain a pure nano-alumina seed intermediate; The fourth washing process involves washing with deionized water five times. 5) The pure nano-alumina seed intermediate, sodium hexametaphosphate, and solvent are mixed and then subjected to a second ultrasonic dispersion and ball milling process to obtain a dispersion slurry. Solvent one includes deionized water; the mass ratio of sodium hexametaphosphate, α-Al2O3 in the pure nano-alumina seed intermediate, and solvent two is (1~3):100:400; the power of the second ultrasonic dispersion is 400W; the time of the second ultrasonic dispersion is 2h; the grinding medium for ball milling includes zirconia balls, the ball-to-material ratio for ball milling is 6:1, the dispersion medium for ball milling includes ethanol, the ball milling speed for ball milling is 400rpm, and the ball milling time for ball milling is 12h; 6) Mix the dispersion slurry with deionized water at a mass ratio of 1:9, and then perform a third ultrasonic dispersion and a first centrifugation treatment in sequence. Take the supernatant to obtain nano-alumina seed crystals.

[0116] The third ultrasonic dispersion power was 400W; the third ultrasonic dispersion time was 30min; the first centrifugation speed was 10000rpm; the first centrifugation time was 20min; and the nano alumina seed crystals were α-Al2O3 transparent hydrosol seed crystals with a solid content of 8% and an average particle size of 5nm~20nm.

[0117] The preparation method of microemulsion includes the following steps: (1) Mix 18.7g of composite surfactant, 310mL of cyclohexane and second ammonia water to obtain a mixture; The composite surfactant consists of 14g of sorbitan monooleate and 4.7g of polyoxyethylene sorbitan monooleate, with a mass ratio of 3:1; the mass ratio of the composite surfactant to cyclohexane is 6.03g:100mL; and the second ammonia solution is a mixture of 34mL of deionized water and 6mL of 0.7mol / L dilute ammonia solution.

[0118] (2) The mixture was ultrasonically emulsified, and then 2.5g of polyethylene glycol 400 was added to obtain a microemulsion; The ultrasonic emulsification temperature was 32℃, the ultrasonic emulsification time was 15min, the ultrasonic emulsification power was 250W, and the ultrasonic emulsification frequency was 40kHz; the average particle size of the micro water nuclei in the microemulsion was 13nm.

[0119] Step 2: The aluminum alkoxide solution, seed crystal solution, and microemulsion are mixed to obtain a composite phase mixture; The first mixing method includes the following steps: aluminum alkoxide solution and seed crystal solution are simultaneously pumped into the microemulsion through a dual-channel microreactor; the inner diameter of the dual-channel microreactor is 1.2 mm; The flow rate of the aluminum alkoxide solution was 3 mL / min, and the flow rate of the seed crystal solution was 4.5 mL / min; the volumetric flow rate ratio of the aluminum alkoxide solution to the seed crystal solution was 1:1.5. The residence time of the aluminum alkoxide solution in the dual-channel microreactor for controlled hydrolysis was 10 min; the residence time of the seed crystal solution in the dual-channel microreactor for controlled hydrolysis was 5 min.

[0120] Step 3: Perform a controlled hydrolysis reaction on the intermediate of the composite phase mixture to obtain a hydrolyzed mixture; mix the hydrolyzed mixture with the separating phase evenly (stir for 40 min) to obtain a composite phase mixture; The pH value of the controlled hydrolysis reaction is 8.6~9.4; the pH value of the controlled hydrolysis reaction is adjusted by adjusting the feed flow rate of the seed crystal solution; the temperature of the controlled hydrolysis reaction is 45℃; the time of the controlled hydrolysis reaction is 2.5h; the controlled hydrolysis reaction is carried out under stirring, and the stirring speed is 400rpm. The isolating phase is 80g of ammonium sulfate, and the molar ratio of ammonium sulfate to aluminum ions in the aluminum alkoxide solution is approximately 18:1.

[0121] Step 4: Centrifuge the composite phase mixture to demulsify it, and obtain the first solid phase, the first liquid phase, and the oil phase. The stirring rate for centrifugal demulsification was 4000 rpm; the centrifugal demulsification time was 10 min. Step 5: The first solid phase is subjected to a first washing treatment and a spray drying treatment in sequence to obtain the precursor composite powder; The first washing process involves washing three times with deionized water; the inlet temperature of the spray dryer is 190℃, and the outlet temperature of the spray dryer is 85℃. Step 6: Under an air atmosphere with a flow rate of 100 mL / min, the precursor composite powder is subjected to gradient calcination to obtain a high-purity nano-monodisperse alumina intermediate. The gradient calcination process includes sequentially performing a first calcination, a second calcination, and a third calcination on the precursor composite powder. The heating rate for the first calcination was 2.5℃ / min; the calcination temperature for the first calcination was 420℃; and the calcination time for the first calcination was 1.2h. The heating rate for the second calcination was 3.5℃ / min; the calcination temperature for the second calcination was 820℃; and the calcination time for the second calcination was 1.2h. The heating rate for the third calcination was 6℃ / min; the calcination temperature for the third calcination was 1090℃; and the calcination time for the third calcination was 3h. Step 7: Purify the high-purity nano-monodisperse alumina intermediate to obtain high-purity nano-monodisperse alumina.

[0122] The purification process includes the following steps: performing a second washing treatment and an acid washing treatment on the high-purity nano-monodisperse alumina intermediate to obtain a second solid phase and a second liquid phase; performing a second centrifugation treatment and an acid washing treatment on the second solid phase to obtain a third solid phase and a third liquid phase; and performing freeze-drying treatment on the third solid phase to obtain high-purity nano-monodisperse alumina.

[0123] The second washing process involved washing with deionized water four times; the second centrifugation process involved stirring at 3500 rpm for 7 minutes; both the first and second acid washing processes used dilute hydrochloric acid with a pH of 4 for 20 minutes each; the freeze-drying process was carried out at -48°C with a vacuum degree ≤10 Pa for 18 hours.

[0124] The high-purity nano-monodisperse alumina was prepared by the above method; Characterization: ICP-OES analysis showed that the purity of the high-purity nano-monodisperse alumina was 99.993%. XRD analysis showed that the high-purity nano-monodisperse alumina was a pure α-Al2O3 phase; By mass percentage, the α-Al₂O₃ phase of high-purity nano-monodisperse alumina is ≥98%; the α-phase conversion rate is 99.5%. By mass percentage, the high-purity nano-monodisperse alumina contains 38 ppm Na2O, 22 ppm Fe2O3, and 32 ppm SiO2.

[0125] FE-SEM testing showed that the average particle size of the primary particles of high-purity nano-monodisperse alumina was 26 nm. Laser particle size analysis showed that the secondary particles D of high-purity nano-monodisperse alumina... 50 The particle size is 62nm, D 10 =34nm, D 90 =76nm, the particle size distribution ratio D of secondary particles 90 / D 10 The ratio is 2.24; the particle size distribution dispersion index (PDI) of high-purity nano-monodisperse alumina is 0.088. The specific surface area of ​​high-purity nano-monodisperse alumina is 52 m². 2 ·g -1 .

[0126] Comparative Example 1 Comparative Example 1 provides a method for preparing high-purity nano-monodisperse alumina, comprising the following steps: Step 1: Provide an aluminum alkoxide solution and a seed solution consistent with those in Example 1; The preparation methods and parameters of the aluminum alkoxide solution and the seed solution are the same as those in Example 1, and will not be repeated here.

[0127] Step 2: Add aluminum alkoxide solution dropwise to the seed crystal solution for mixing to obtain a composite phase mixture; Step 3: React the intermediate of the composite phase mixture to obtain the composite phase mixture; The reaction temperature was 50℃; the reaction time was 2 hours; the reaction was carried out under stirring at a stirring rate of 500 rpm.

[0128] The specific process steps and parameters for steps four through seven are the same as those in Example 1, and will not be repeated here.

[0129] The high-purity nano-monodisperse alumina was prepared by the above method; Characterization: ICP-OES analysis showed that the purity of the high-purity nano-monodisperse alumina was 99.985%. By mass percentage, the α-Al2O3 phase of high-purity nano-monodisperse alumina is ≥98%.

[0130] By mass percentage, the content of Na2O in high-purity nano-monodisperse alumina is ≤50ppm, the content of Fe2O3 is ≤30ppm, and the content of SiO2 is ≤50ppm.

[0131] Laser particle size analysis showed that the secondary particles D of high-purity nano-monodisperse alumina... 50 The particle size is 350 nm; the particle size distribution dispersion index (PDI) of high-purity nano-monodisperse alumina is 0.55. The specific surface area of ​​high-purity nano-monodisperse alumina, measured by the BET method, is 15 m². 2 ·g -1 .

[0132] In addition, electron microscopy analysis was performed on the precursor powder and the final product. Transmission electron microscopy (TEM) results showed that the boehmite precursor had an irregular morphology and obvious agglomeration. After high-temperature calcination, the sample was transformed into a dense blocky product.

[0133] The difference between Comparative Example 1 and Example 1 is that there is no microemulsion confined hydrolysis. It can be seen that microemulsion confined hydrolysis is a necessary means to solve the technical problem of "precise controllable precursor particle size".

[0134] Comparative Example 2 Comparative Example 2 provides a method for preparing high-purity nano-monodisperse alumina, which differs from Example 1 in that no seed solution is added.

[0135] The remaining steps and parameters are the same as in Example 1, and will not be repeated here.

[0136] The high-purity nano-monodisperse alumina was prepared by the above method; Characterization: ICP-OES analysis showed that the purity of the high-purity nano-monodisperse alumina was 99.99%. XRD analysis showed that the high-purity nano-monodisperse alumina consisted of α-Al₂O₃ and θ-Al₂O₃ phases; the conversion rate of the α phase was approximately 85%. FE-SEM testing showed that the primary particle size of high-purity nano-monodisperse alumina was 20nm~12nm (non-uniform). Laser particle size analysis showed that the secondary particles D of high-purity nano-monodisperse alumina... 50 The particle size is 150 nm; the particle size distribution dispersion index (PDI) of high-purity nano-monodisperse alumina is 0.35. The specific surface area of ​​high-purity nano-monodisperse alumina, measured by the BET method, is 22 m². 2 ·g -1 .

[0137] The difference between Comparative Example 2 and Example 1 is that no seed solution was added. According to the results, it can be seen that introducing ultrafine seeds for induction is a necessary technical means to solve technical problems such as high α-phase transformation temperature and abnormal grain coarsening.

[0138] Comparative Example 3 Comparative Example 3 provides a method for preparing high-purity nano-monodisperse alumina, which differs from Example 1 in that ammonium sulfate is not added.

[0139] The remaining steps and parameters are the same as in Example 1, and will not be repeated here.

[0140] The high-purity nano-monodisperse alumina was prepared by the above method; Characterization: ICP-OES analysis showed that the purity of the high-purity nano-monodisperse alumina was 99.991%. FE-SEM testing showed that the average particle size of the primary particles of high-purity nano-monodisperse alumina was 20nm~50nm; Laser particle size analysis showed that the secondary particles D of high-purity nano-monodisperse alumina... 50 The particle size is 220 nm; the particle size distribution dispersion index (PDI) of high-purity nano-monodisperse alumina is 0.48. The specific surface area of ​​high-purity nano-monodisperse alumina, measured by the BET method, is 16 m². 2 ·g -1 .

[0141] In addition, electron microscopy analysis of this product showed that a large number of sintered necks were formed between the particles, exhibiting chain-like and network-like agglomerations.

[0142] The difference between Comparative Example 3 and Example 1 is that ammonium sulfate was not added. This shows that even with microemulsion confinement and seed induction by seed solution, hard agglomeration is still inevitable during high-temperature α-phase transformation if the physical barrier of the salt isolation phase is lacking. This indicates that the ammonium sulfate isolation phase is a necessary means to solve the technical problem of "calcination hard agglomeration".

[0143] Comparative Example 4 Comparative Example 4 provides a method for preparing high-purity nano-monodisperse alumina, which differs from Example 1 in that ammonium sulfate is replaced with sodium sulfate; wherein the molar ratio of sodium sulfate to aluminum ions in the aluminum alkoxide solution is 22:1.

[0144] The remaining steps and parameters are the same as in Example 1, and will not be repeated here.

[0145] The high-purity nano-monodisperse alumina prepared by the above method Characterization: ICP-OES analysis showed that the purity of the high-purity nano-monodisperse alumina was 99.96%. By mass percentage, the α-Al2O3 phase of high-purity nano-monodisperse alumina is ≥98%.

[0146] By mass percentage, the high-purity nano-monodisperse alumina contains 280 ppm Na2O, 45 ppm Fe2O3, and 32 ppm SiO2.

[0147] FE-SEM testing showed that the average particle size of the primary particles of high-purity nano-monodisperse alumina was 35 nm. Laser particle size analysis showed that the secondary particles D of high-purity nano-monodisperse alumina... 50 The particle size is 80 nm; the particle size distribution dispersion index (PDI) of high-purity nano-monodisperse alumina is 0.13. The specific surface area of ​​high-purity nano-monodisperse alumina, measured by the BET method, is 12.6 m². 2 ·g -1 .

[0148] The difference between Comparative Example 1 and Example 1 is that sodium sulfate was used instead of ammonium sulfate. It can be seen that although sodium sulfate has a certain isolating effect, the sodium ions introduced into the system are difficult to completely elute, resulting in the product purity not meeting the 4N standard. This confirms that using ammonium sulfate, which has no alkali metal cations, is the core solution to overcome the technical bias of the difficulty in simultaneously achieving salt isolation phase and 4N high purity, and is also an essential technical condition for preparing 4N-grade high-purity products in this application.

[0149] Comparative Example 5 Comparative Example 5 provides a method for preparing high-purity nano-monodisperse alumina, which differs from Example 1 in that the parameters of the third calcination are different. In Comparative Example 5, the heating rate of the third calcination is 10℃ / min; the calcination temperature of the third calcination is 1250℃; and the calcination time of the third calcination is 1h.

[0150] The remaining steps and parameters are the same as in Example 1, and will not be repeated here.

[0151] The high-purity nano-monodisperse alumina was prepared by the above method; Characterization: ICP-OES analysis showed that the purity of the high-purity nano-monodisperse alumina was 99.989%. XRD analysis showed that the high-purity nano-monodisperse alumina was a pure α-Al2O3 phase; By mass percentage, the high-purity nano-monodisperse alumina contains ≥98% α-Al₂O₃ phase; the α-phase conversion rate is 100%. By mass percentage, the content of Na2O in high-purity nano-monodisperse alumina is ≤35ppm, the content of Fe2O3 is ≤30ppm, and the content of SiO2 is ≤38ppm.

[0152] FE-SEM testing showed that the average particle size of the primary particles of high-purity nano-monodisperse alumina was 55 nm. Laser particle size analysis showed that the secondary particles D of high-purity nano-monodisperse alumina... 50 The particle size is 180 nm; the particle size distribution ratio D of the secondary particles 90 / D 10 The ratio is <2.5; the particle size distribution dispersion index (PDI) of high-purity nano-monodisperse alumina is 0.32. The specific surface area of ​​high-purity nano-monodisperse alumina, measured by the BET method, is 20 m². 2 ·g -1 .

[0153] In addition, electron microscopy analysis of the product revealed obvious sintering necks between particles, forming chain-like aggregates.

[0154] Comparing Example 1 and Comparative Example 5, it can be seen that although a higher calcination temperature can completely transform the α phase, a temperature exceeding 1120°C can easily lead to premature volatilization of the ammonium sulfate separator, a decrease in viscosity, and failure of physical separation, thus causing sintering and growth between the product particles.

[0155] In summary, this invention provides a high-purity nano-monodisperse alumina and its preparation method. The high-purity nano-monodisperse alumina has a purity ≥99.99%, with α-Al₂O₃ phase ≥98% and a particle size distribution dispersion index (PDI) ≤0.10. This high-purity, excellent particle dispersibility, and regular morphology meet the requirements of high-end high-purity powder applications such as electronic ceramics and precision polishing. The preparation method involves placing an aluminum alkoxide solution and a seed crystal solution in a microemulsion for controlled hydrolysis, followed by centrifugal demulsification, gradient calcination, and purification treatment to finally obtain high-purity nano-monodisperse alumina with a purity ≥99.99%. The method utilizes a triple synergistic mechanism of microemulsion spatial confinement hydrolysis, ultrafine seed crystal-induced directional crystal phase transformation, and an alkali-free molten salt isolation layer to prevent agglomeration, achieving the preparation of 4N-level monodisperse nano-α-Al₂O₃ powder with no hard agglomeration and a spherical morphology under relatively low temperature conditions.

[0156] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.

Claims

1. A high-purity nano-monodisperse alumina, characterized in that, The purity of the high-purity nano-monodisperse alumina is ≥99.99%; The high-purity nano-monodisperse alumina contains ≤50ppm Na2O, ≤30ppm Fe2O3, and ≤50ppm SiO2 by mass percentage. The high-purity nano-monodisperse alumina comprises ≥98% α-Al2O3 by mass percentage.

2. The high-purity nano-monodisperse alumina according to claim 1, characterized in that, The primary particles of the high-purity nano-monodisperse alumina have an average particle size of 20nm~50nm, and the secondary particles of the high-purity nano-monodisperse alumina have a diameter of D... 50 Particle size of 50nm~100nm; and / or, The particle size distribution ratio D of the secondary particles of the high-purity nano-monodisperse alumina 90 / D 10 The ratio is <2.5; and / or, The high-purity nano-monodisperse alumina has a particle size distribution dispersion index (PDI) ≤ 0.10; and / or, The specific surface area of ​​the high-purity nano-monodisperse alumina is 30 m². 2 ·g -1 ~60m 2 ·g -1 .

3. A method for preparing high-purity nano-monodisperse alumina according to claim 1 or 2, characterized in that, Includes the following steps: An aluminum alkoxide solution, a seed crystal solution, and a microemulsion are provided. The aluminum alkoxide solution, the seed crystal solution, and the microemulsion are first mixed to obtain a composite phase mixture intermediate. The intermediate of the composite phase mixture is subjected to a controlled hydrolysis reaction to obtain a hydrolyzed mixture; The hydrolyzed mixture is mixed with the isolated phase to obtain a composite phase mixture; The composite phase mixture was centrifuged and demulsified to obtain a first solid phase, a first liquid phase, and an oil phase. The first solid phase is subjected to a first washing treatment and a spray drying treatment in sequence to obtain the precursor composite powder; The precursor composite powder was subjected to gradient calcination to obtain a high-purity nano-monodisperse alumina intermediate. as well as, The high-purity nano-monodisperse alumina intermediate was purified to obtain the high-purity nano-monodisperse alumina.

4. The method for preparing high-purity nano-monodisperse alumina according to claim 3, characterized in that, The atmosphere for the gradient calcination treatment includes either an air atmosphere or an oxygen atmosphere; and / or, The gradient calcination process includes sequentially subjecting the precursor composite powder to a first calcination, a second calcination, and a third calcination. The heating rate of the first calcination is 2℃ / min to 5℃ / min; the calcination temperature of the first calcination is 400℃ to 500℃; and the calcination time of the first calcination is 1h to 2h. The heating rate of the second calcination is 3℃ / min~5℃ / min; the calcination temperature of the second calcination is 800℃~900℃; and the calcination time of the second calcination is 1h~2h. The heating rate of the third calcination is 6℃ / min~7℃ / min; the calcination temperature of the third calcination is 1080℃~1120℃; and the calcination time of the third calcination is 2.5h~3.5h.

5. The method for preparing high-purity nano-monodisperse alumina according to claim 3, characterized in that, The first mixing method includes the following steps: simultaneously pumping the aluminum alkoxide solution and the seed crystal solution into the microemulsion through a dual-channel microreactor; The inner diameter of the dual-channel microreactor is 0.5 mm to 2.0 mm; The volumetric flow rate ratio of the aluminum alkoxide solution to the seed crystal solution is 1:(1.2~2.0); the residence time of the aluminum alkoxide solution in the dual-channel microreactor during the controlled hydrolysis reaction is 5 min~15 min; the residence time of the seed crystal solution in the dual-channel microreactor during the controlled hydrolysis reaction is 5 min~15 min; and / or, The pH value of the controlled hydrolysis reaction is 8.5~10.5; the pH value of the controlled hydrolysis reaction is adjusted by: adjusting the feed flow rate of the seed crystal solution; and / or, The controlled hydrolysis reaction is carried out at a temperature of 40℃~60℃; and / or, The controlled hydrolysis reaction takes place over a period of 1 to 3 hours; and / or, The controllable hydrolysis reaction is carried out under stirring conditions, and the stirring rate under stirring conditions is 300 rpm to 800 rpm.

6. The method for preparing high-purity nano-monodisperse alumina according to claim 3, characterized in that, The isolating phase comprises ammonium sulfate; and / or, The molar ratio of the isolating phase to the aluminum ions in the aluminum alkoxide solution is (15~30):1; and / or, The stirring rate for the centrifugal demulsification process is 3000 rpm to 5000 rpm; and / or, The centrifugal demulsification process is performed for 5 to 10 minutes; and / or, The inlet temperature of the spray dryer is 180℃~220℃; and / or, The outlet temperature of the spray dryer is 80℃~100℃.

7. The method for preparing high-purity nano-monodisperse alumina according to claim 3, characterized in that, The purification process includes the following steps: The high-purity nano-monodisperse alumina intermediate is subjected to a second washing treatment and an acid washing treatment to obtain a second solid phase and a second liquid phase. The second solid phase is subjected to a second centrifugation treatment and a second acid washing treatment to obtain a third solid phase and a third liquid phase; The third solid phase was freeze-dried to obtain the high-purity nano-monodisperse alumina. The reagents for both the first and second acid pickling treatments include an acid solution; the acid solution includes either dilute nitric acid or dilute hydrochloric acid; the pH value of the acid solution is 3-4; and the time for both the first and second acid pickling treatments is 10-30 minutes. The freeze-drying process is carried out at a temperature of -50℃ to -40℃, with a vacuum degree of ≤10Pa and a duration of 24h to 48h.

8. The method for preparing high-purity nano-monodisperse alumina according to claim 3, characterized in that, The method for preparing the aluminum alkoxide solution includes the following steps: Aluminum metal was mixed with isopropanol and subjected to reflux and vacuum distillation sequentially to obtain aluminum isopropoxide; and, The aluminum isopropoxide is mixed with anhydrous isopropanol to obtain the aluminum alkoxide solution; Wherein, the purity of the aluminum metal is ≥99.999%; The vacuum degree of the vacuum distillation process is ≤100Pa; the fraction collected at 135℃~140℃ during the vacuum distillation process is used as aluminum isopropoxide; The purity of the aluminum isopropoxide is ≥99.999%; the total amount of Si, Fe, Na, Ca, Mg, Cu, Ti, Cr, Mn and Zn in the aluminum isopropoxide is ≤10ppm by mass percentage. The aluminum ion concentration in the aluminum alkoxide solution is 0.05 mol / L to 0.2 mol / L; The mass ratio of aluminum isopropoxide to anhydrous isopropanol is 1:(8~20).

9. The method for preparing high-purity nano-monodisperse alumina according to claim 3, characterized in that, The seed solution includes an alkaline solution containing nano-alumina seeds, and the alkaline solution containing nano-alumina seeds includes an ammonia solution containing nano-alumina seeds. The preparation method of the ammonia solution containing nano-alumina seeds includes the following steps: mixing nano-alumina seeds with a first ammonia solution to obtain the ammonia solution containing nano-alumina seeds; The concentration of the first ammonia solution is 0.5 mol / L to 2.0 mol / L; the nano-alumina seed crystals are α-Al2O3 transparent hydrosols with a solid content of 5% to 10% and an average particle size of 5 nm to 20 nm; the mass ratio of Al2O3 in the nano-alumina seed crystals to the ammonia solution containing the nano-alumina seed crystals is (0.5 to 3):

100.

10. The method for preparing high-purity nano-monodisperse alumina according to any one of claims 3 to 9, characterized in that, The method for preparing the microemulsion includes the following steps: A mixture was prepared by mixing a composite surfactant, cyclohexane, and a second ammonia solution; and, The mixture is ultrasonically emulsified, and then a co-surfactant is added to obtain the microemulsion. The composite surfactant comprises sorbitan monooleate and polyoxyethylene sorbitan monooleate; the mass ratio of sorbitan monooleate to polyoxyethylene sorbitan monooleate is (3~5):

1. The mass ratio of the composite surfactant to the cyclohexane is (5~12) g: 100 mL; The total volume ratio of the composite surfactant and the second ammonia water to the volume ratio of the cyclohexane is 1:(8~15); The concentration of the second ammonia solution is 0.0455 mol / L to 0.4286 mol / L; The temperature for ultrasonic emulsification is 30℃~40℃; The ultrasonic emulsification time is 10 min to 30 min; The power of the ultrasonic emulsification is 200W~400W; The frequency of the ultrasonic emulsification is 40 kHz; The average particle size of the micro-water nuclei in the microemulsion is 10 nm to 20 nm. The co-surfactant includes polyethylene glycol 400; The mass ratio of the co-surfactant to the cyclohexane is (1~3) g: 100 mL.